There Was No Evidence of Osteonecrosis in Lunates of Early-Stage Kienbock’s Disease - Hwang, Ji Sup; Kim, Jihyeung; Gong, Hyun Sik; Kim, Jin Ho; Baek, Goo Hyun; Kim, Hee Joong (Clinics in orthopedic surgery, 2025)
Background: The etiology and pathogenesis of Kienbock’s disease (KD) have not been clearly established. In osteonecrosis of other bones, such as the proximal femur, the interface between necrotic and normal bone is evident in early stages. The purpose of this study was to retrospectively review and analyze magnetic resonance (MR) images of early-stage KD to confirm whether the double-line sign or an abnormal signal intensity band corresponding to the reactive interface is present. Methods: We retrospectively reviewed 31 cases of 30 patients (average age, 41.2 years) diagnosed with early-stage KD. Lichtman staging revealed 9 cases of stage I and 22 cases of stage II. We evaluated their MR images of various sequences with special interest in signal intensity changes and the presence of the double-line sign. Results: In all lunates, no abnormal signal intensity band representing a reactive interface was observed. Instead, diffuse signal intensity changes with a bone marrow edema pattern (BMEP) of various extents were detected in all 31 lunates. Furthermore, a fracture line was found in 10 lunates and BMEP in the surrounding carpal bones was present in 8 cases. Conclusions: In lunates with stage I and II KD, the main MR finding was diffuse BMEP without an abnormal signal intensity line of a reactive interface, and some cases showed abnormal signal intensity bands suggestive of a fracture line. KCI Citation Count: 0